ECONOMIC ASPECTS OF APPLICATION OF THE RUSSIAN BIOSIMILAR OMALIZUMAB IN PATIENTS WITH ATOPIC BRONCHIAL ASTHMA OF MODERATE TO SEVERE CLINICAL COURSES - V. S. Krysanova; E. D. Ermolaeva; T. N. Ermolaeva; M. V. Davydovskaya; K. A. Kokushkin (Фармация и фармакология (Пятигорск))
A certain success in the treatment of bronchial asthma is associated with the introduction of monoclonal antibodies into the treatment process. They made it possible to improve the control of the disease. A number of original genetically engineered biological drugs, such as benralizumab, reslizumab, dupilumab, mepolizumab and omalizumab, are currently registered in Russia. In 2020, this list was supplemented by the first Russian biosimilar drug omalizumab – Genolar® (JSC Generium, Russia). High rates of the development of modern medicine are closely related to the use of biosimilars. The prescription of biosimilars today often makes it possible to provide a larger number of patients with modern drugs at lower costs.The aim of the study was a comprehensive pharmacoeconomic assessment of the application of the domestic biosimilar drug omalizumab in the treatment of patients suffering from moderate and severe atopic bronchial asthma.Materials and methods. At the first stage, an information search in the available databases (Cochrane Library, MedLine, Embase, eLIBRARY) was carried out. According to the results obtained, a meta-analysis (Agache I. et al.) was found out; within its framework, the efficacy and safety of the use of several monoclonal antibodies was assessed. Dupilumab was chosen as the reference drug. Pharmacoeconomic analyses were carried out using a “Cost-Minimization Analysis” (CMA) and a “Budget Impact Analysis” (BIA). Taking into account various options of bronchial asthma, the developed algorithm for providing medical care to adult patients with atopic asthma made it possible to assess the costs, including direct medical and indirect costs.Results. The cost analysis demonstrated the advantage of using the Russian biosimilar omalizumab in patients with atopic asthma compared to dupilumab due to financial savings of up to 40%. The Budget Impact Analysis showed that the use of the domestic biosimilar omalizumab, even taking into account the annual increase in the number of patients (8%), will save up to 109,641,409.64 rubles (or 3%) compared to the current practice.Conclusion. The use of the domestic biosimilar omalizumab in patients with moderate to severe atopic bronchial asthma is a clinically effective and economically justified approach to organizing medical care for adult patients in Russia.